THE EFFECT OF SUMMARIZING TECHNIQUE ON READING ACHIEVEMENT - Siti Syafi’atul Qomariyah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This article is a report of experimental conducted at the second year students of SMA Kanjeng Sepuh Sidayu Gresik. This study was conducted to measure the effect of summarizing technique on reading achievement. The instrument used for collecting data was test. The data analysis showed that mean of pretest was 37,94 in experimental group and 33,68 in control group. The result of t-test of pre-test was 2,444 and t-critical was 1,684 in level of significant .05. And the mean of post-test was 74,52 in experimental group and 68,39 in control group. The difference between the two mean score is 6.13. The mean of the control group is lower than the experimental one. In which the highest score was 52 and the lowest score was 20 in control group and experimental group. From the data analysis, the writer got findings. The mean score of experimental group was 74.52 and the mean score of control group was 68.39. after applying the ANCOVA formula, it indicates that F-value was 4.117 and the critical value with the level of significance .05 was 4.00. The finding shows that students’ achievement of reading in posttest (after treatment) of experimental group was higher than control group. It was found out that summarizing technique was effective in reading achievement.